PEMANFAATAN TUMBUHAN OBAT OLEH MASYARAKAT DESA GUNUNG SEMBILAN KECAMATAN SUKADANA KABUPATEN KAYONG UTARA - Sauji, muhamad; Oramahi, H A; Idham, M (Universitas Tanjungpura, 2019)
Medicinal plants are one of the important components in medicine, in the form of traditional herbal concoctions and have been used since hundreds of years ago, to solve various health problems. This study aims to obtain the spesies of traditional medicinal plants used by the community in Gunung Sembilan Village in treating diseases and to know the use of medicinal plants and how to concoct medicinal raw materials. Data collection with interview and determination of responden uses a snowball sampling technique or carried out sequentially by asking for information on people who have been interviewed or contacted before the research. Observations were made, namely by walking while (without plots) making direct observations in the field together with respondents who knew about the medicinal plants. The results of interviews with the community of Gunung Sembilan Village, Sukadana District North Kayong Regency, 27 species of medicinal plants and 23 families were utilized by the community. The use of herbs is single or mixed, the most widely used are leaves (10 species or 37.04%). The most commonly used processing method is pounded (12 species or 44.44%), and how to consume the most frequently done, which is drink (12 species or 44.44%).Keywords : Gunung Sembilan village community, medicinal plants.